Urinary mRNA-based biomarkers for non-muscle-invasive bladder cancer: a mini-review - Coelho, Karoline Brito Caetano Andrade; Wosniaki, Denise Kusma; Marin, Anelis Maria; Fabris, Laura; Borges dos Reis, Rodolfo; Aoki, Mateus Nóbrega; Zanette, Dalila Lucíola (Frontiers in Oncology, 2024)
Bladder cancer (BC) is the second most common type of cancer of the urinary system.Approximately 75% of the cases are non-muscle invasive bladder cancer (NMIBC), which has a high recurrence and progression rate. Current diagnosis and surveillance methods present challenges, including risks to the patients. For this reason, urinary biomarkers have been proposed as alternatives to the methods. The goal of this minireview is to describe urinary mRNA-based biomarkers available in current literature for NMIBC tumors, using the PubMed database. The search included the following keywords: "biomarkers" AND "bladder cancer" AND "urine" and "RNA" and "nonmuscle". The search yielded 11 original researchers utilizing mRNA-based urinary biomarkers. Although there is a wide variety of biomarkers described, the cohorts of the studies were not exclusively NMIBC, which is the subtype of BC that would mostly benefit from the introduction of a good follow-up biomarker, highlighting the need for randomized interventional trials for NMIBC.